A new method for estimating the scale of fluctuation in reliability assessment of reinforced concrete structures considering spatial variability. Issue 13 (October 2018) - Yang, Yiming; Peng, Jianxin; Zhang, Jianren; Cai, CS
The scale of fluctuation ( θ ) of the material and geometrical parameters is the basis of studying the spatial variability of reinforced concrete structures. In this article, a new estimation method for the scale of fluctuation based on Bayesian information criterion is proposed. And based on the analysis of experimental data recorded on the three 36-year-old beams of the Jianggong Bridge and 246 corroded steel bars, the scale of fluctuation ( θ ) of concrete compressive strength ( fc ) and steel pitting factor ( R ) are estimated. The theoretical bending moment of three test beams are calculated considering the influence of the spatial distributions of fc, R, and other relative variables. The reasonableness and superiority of the Bayesian information criterion model than the auto-correlation function method and the semivariogram function model are verified by comparing the theoretical results with the measured bending moment of the three beams mentioned above.